Фазовые превращения в CdAs₂ и ZnAs₂ при высоком давлении - Моллаев, А.Ю.; Арсланов, Р.К.; Сайпулаева, Л.А.; Бабушкин, А.Н.; Лях, Т.С.; Татур, С.В.; Маренкин, С.Ф.; Михайлов, С.Г. (Физика и техника высоких давлений, 2005)
На ориентированных монокристаллах CdAs₂ и ZnAs₂ измерены удельное электросопротивление и коэффициент Холла при гидростатическом давлении до 9 GPa и определены барические зависимости электросопротивления при квазигидростатике до 50 GPa. В CdAs₂ на барических зависимостях электросопротивления и коэффициента Холла при подъеме давления при P ≈ 5.5 GPa наблюдаются фазовые переходы, положения которых не зависят от кристаллографической ориентации образца. В ZnAs₂ предполагается наличие двух фазовых переходов: 1) в диапазоне давлений P = 10–15 GPa и 2) при P = 25−30 GPa. In the oriented monocrystals of CdAs₂ and ZnAs₂ there have been measured the specific resistance and Hall coefficient at the hydrostatic pressure up to 9 GPa and baric dependences of electrical resistance at the quasi-hydrostatics up to 50 GPa have been determined. Phase transitions whose locations are independent of the crystallographic orientation of the sample have been observed in CdAs₂ on the baric dependences of electrical resistance and Hall coefficient at pressure rise for P ≈ 5.5 GPa. Two phase transitions have been supposed to be in ZnAs₂, the first one in the pressure range P = 10−15 GPa and the second one at P = 25−30 GPa.